IMPROVING STUDENTS CRITICAL THINKING SKILLS ON STUDENT LEARNING OUTOCOMES USING THE ICARE STRATEGY - Tarigan, Mei Cristin; Sinuraya, Juru Bahasa (UNIVERSITAS NEGERI MEDAN, 2024)
This study aims to determine the level of students' critical thinking skills and train critical thinking skills of students in class X IPA SMA Swasta Taman Siswa Medan on Newton's Law material. This type of research is a pseudo experiment. The population in this study were all students of class X IPA SMA Swasta Taman Siswa Medan. This sampling uses the Total Sampling technique by taking all X IPA class students. The instruments used in this study consisted of two types, namely instruments to determine learning outcomes and activities with test instruments, the pretest value of the experimental class was 46 19 and the control class was 42.73 and after the learning was completed a posttest was given with the results of the experimental class posttest value of 85.48 and the control class of 72.73, so that there was a significant effect of the ICARE learning strategy on students' critical thinking skills on the subject matter of Newton's law.